Nonformal education a handbook for teacher education students, NFE administrators and extension program implementors - Cabag, Ramon C. (Katha Pub., 1999)
This book has four parts. Part one introduces the nonformal program, its nature, scope, characteristics and principles. Part two discusses the "education for all" Philippine plan of action. Part three presents the characteristics of the nonformal education learners and teachers and principles of adult teaching, as well as contemporary approaches or methods and other strategies. Part four provides reason why the nonformal education program should be evaluated.